Cervical Spinal Osteomyelitis with Epidural Abscess following an Escherichia coli Urinary Tract Infection in an Immunocompetent Host - Abdelmoniem Moustafa; Rowida Kheireldine; Zubair Khan; Hussam Alim; Mohammad Saud Khan; Mohd Amer Alsamman; Eslam Youssef (Case Reports in Infectious Diseases)
Spinal epidural abscess (SEA) is uncommon with an incidence reported as 0.33–1.96 abscesses per 10,000 hospital admissions per year. Two-thirds of the cases were caused by Staphylococcus aureus. Escherichia coli (E. coli) is a less common cause of SEA, and it is usually after urinary tract infection in patient with preexisting risk factor. A 69-year-old male with a past medical history significant for prostatitis was admitted with fever, altered mental status, neck pain, progressive lower extremities weakness, and frequent falls for 7 days. Both blood and urine cultures grew E. coli. Lumbar puncture showed 94 RBCs, 24 WBCs (16% neutrophils and 46% lymphocytes), and elevated protein level at 1140 mg/dl with no bacteria. C-spine MRI showed epidural abscess along the anterior and right lateral margin of the cord causing cord compression from C5 through C7, anterior perivertebral abscess from C4 through T2, marrow edema involving C6 and C7 vertebral bodies with increased signal in the intervertebral disc space at C6-C7, and consistent with osteomyelitis and discitis. Anterior cervical decompression with evacuation of anterior epidural abscess with fusion was done. The culture from the epidural abscess grew E coli. A diagnosis of SEA should be considered in patients presenting with progressive weakness and neurological deficits following UTI and is to be confirmed by MRI. E. coli could be the culprit for epidural abscess and spine osteomyelitis even in immunocompetent patients.